2016
DOI: 10.1189/jlb.3ru1015-451r
|View full text |Cite
|
Sign up to set email alerts
|

A matter of time: study of circadian clocks and their role in inflammation

Abstract: Circadian rhythms regulate changes in physiology, allowing organisms to respond to predictable environmental demands varying over a 24 h period. A growing body of evidence supports a key role for the circadian clock in the regulation of immune functions and inflammatory responses, which influence the understanding of infections and inflammatory diseases and their treatment. A variety of experimental methods have been used to assess the complex bidirectional crosstalk between the circadian clock and inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 114 publications
3
49
0
Order By: Relevance
“…Mice show differential resistance against infection at different times of the day. Inflammation, immune resistance, and the severity of autoimmune diseases are also found to vary throughout the day in a rhythmic manner (Carter et al, 2016; Curtis et al, 2014; Cutolo, 2012; Gibbs and Ray, 2013). The chronic disruption of circadian rhythms, including sleep deprivation, shift work, and jet lag can precipitate disease even in healthy individuals and exacerbate existing diseases, particularly inflammatory conditions (Ranjbaran et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mice show differential resistance against infection at different times of the day. Inflammation, immune resistance, and the severity of autoimmune diseases are also found to vary throughout the day in a rhythmic manner (Carter et al, 2016; Curtis et al, 2014; Cutolo, 2012; Gibbs and Ray, 2013). The chronic disruption of circadian rhythms, including sleep deprivation, shift work, and jet lag can precipitate disease even in healthy individuals and exacerbate existing diseases, particularly inflammatory conditions (Ranjbaran et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating clinical and experimental observations supporting the rhythmic nature of immune functions 42,51,52 have raised the issue whether leukocytes possess a molecular oscillator. In 2003, Boivin and colleagues demonstrated that expression of clock genes in human peripheral blood mononuclear cells displays a daily rhythm.…”
Section: Various Leukocytesmentioning
confidence: 99%
“…Together with the shared involvement of circadian disruptions, both MDD and AD have been associated with altered inflammatory states (30, 31). The pro-inflammatory cytokine interleukin 6 (IL-6) (32), which is linked to circadian clock-related inflammation (33), is considered to play a central role in the pathophysiology of MDD and AD (30, 31, 34–39). Indeed, IL-6 has been proposed as a molecular bridge between circadian and inflammatory processes in a chronobiological animal model of depression (40) and is implicated in circadian rhythmicity (41) and in the circadian regulation of sleep drive (42, 43).…”
Section: Introductionmentioning
confidence: 99%